The New Approach of Kotekan | Kotekan Pendekatan Baru - I Gede Ngurah Divo Sentana; I Nyoman Kariasa (Pusat Penerbitan LPPMPP ISI Denpasar, 2022)
Explaination about the exist of music motif part a.k.a motif materials unity, made by a music composing technique its build a music form, its outcome from the composer’s decision to compose or make a music composition with a concepting reference accord to values and materials its composer takes from learn and understand process are the elements that explaining in this article. Things its take from learn and understand process eventually give the composer a way to developing. The composing technique its composer does based on method about how to make a performing artworks by the artists who has so much of experience on performing arts. Accord to understand about how to use that method to make a performing artworks, the composer explain the way to realize this music form composition based on two side, they are about materials its interpretate and the outcome. Composer has a wish that the materials its exist on this article could be a topic discussion again and discuss it with a good mentality, because the composer won’t that every kind of artwork its build by effort, hardwork and sublimation its come from composer’s think, only known as “left extreme” (bad ideology).